#### Answer

$5$

#### Work Step by Step

$d = \sqrt {(x_{2} - x_{1})^{2} + (y_{2} - x_{1})^{2}}$
$d = \sqrt {(4 - 0)^{2} + (0 - -3)^{2}}$
$d = \sqrt {(4)^{2} + (3)^{2}}$
$d = \sqrt {16 + 9}$
$d = \sqrt {25}$
$d = 5$

Published by
Cengage

ISBN 10:
978-1-337-61408-5

ISBN 13:
978-1-33761-408-5

$5$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.